PENGARUH EKOLABEL DAN HARGA TERHADAP PEMBELIAN PRODUK RAMAH LINGKUNGAN - Deva, Sinta Alfina; Maurisni, Putri (Jurnal Daya Saing, 2026)
The purchasing behavior of environmentally friendly products is gaining increasing attention among consumers, particularly among students who are becoming more concerned with sustainability. This study aims to analyze the influence of ecolabel and price on the purchasing behavior of environmentally friendly products among students at the Faculty of Economics, Universitas Pasir Pangarain. This research uses a quantitative approach with descriptive and explanatory research types. The sample consists of 100 students selected using purposive sampling technique. The data analysis tool used is SPSS 26 with multiple linear regression methods to test the influence of ecolabel and price on purchasing decisions. The results show that both variables, ecolabel and price, have a positive and significant effect on the purchasing behavior of environmentally friendly products. The managerial implications of this research suggest that companies should strengthen clear ecolabeling and set appropriate prices to attract more young consumers, especially students, who are increasingly concerned with sustainability